Comparative Genomic and Transcriptomic Analyses of CHHs and Their Putative Receptors in Scylla paramamosain, Portunus trituberculatus, and Eriocheir sinensis - Yang, Yanan; Xu, Yuanfeng; Zhang, Peng; Cui, Zhaoxia; Bao, Chenchang (Frontiers in Marine Science, 2021)
Crustacean hyperglycemic hormone superfamily neuropeptides (CHHs) are typical crustacean eyestalk hormones that include the crustacean hyperglycemic hormone (CHH), moult-inhibiting hormone (MIH), vitellogenesis/gonad-inhibiting hormone (VIH/GIH) and mandibular organ-inhibiting hormone (MOIH), which are divided into two subfamilies: type I CHH (included CHH) and type II CHH (consisting of MIH, VIH/GIH and MOIH). They are involved in various biological activities, such as metabolism, molting, reproduction and osmotic regulation. Discovery of the ion transport peptide (ITP) in insects expanded the members of CHHs and revealed that CHHs are not restricted to crustaceans. In this study, we focused on three economically important crabs: the mud crab, Scylla paramamosain, the swimming crab, Portunus trituberculatus, and the Chinese mitten crab, Eriocheir sinensis. Their genomes, Pacbio full-length transcriptomic data as well as comparative RNA-seq data were obtained and used to analyze the genomic structures and expression patterns of CHHs and their putative receptors through bioinformatic methods. Two type I CHH members (CHH1 and CHH2) were identified, of which CHH1 had two splice variants, CHH1-v1 and CHH1-v2. One copy of type II CHH (MIH) was found in P. trituberculatus and E. sinensis. While most decapods, including S. paramamosain, have two copies of type II CHHs (MIH/VIH), these MIH/VIHs are adjacent to each other on the same chromosome. Besides type I and II CHH, ITP-like peptides have also been found in the three crabs, and they are mainly expressed in the eyestalk. Four, five and three G protein-coupled receptors (GPCRs) were identified in S. paramamosain, P. trituberculatus and E. sinensis, respectively, which might be putative CHH receptors. These GPCRs were divided into three groups. One group was composed of two contiguous genomic position GPCRs, and they were mainly expressed in the hepatopancreas. These findings provide a basis for further studies on CHHs receptor binding tests and on CHHs/GPCRs signaling pathways.